Indonesia Baru di Tengah Pertarungan Antara Mosaik Budaya Yang Elok dan Kaya Dengan Ancaman Keserakahan - Ahmad Syafii Maarif (Millah: Journal of Religious Studies, 2005)
This paper is a sorrow reflection of writer toward the paradox reality of Indonesian people, which in one hand known as the religious society, granted by God the beautiful and wealth nature, but in other hand it was treated by greedy and corruptedbureaucracy. The big question of writer, why it happened, the religious Indonesian people couldn't look after the motherland of Indonesia, founded by the sacrifice of founding fathers of this nation? Actually, the writer argues that the religious quality ought to seem on moral quality in relation with among people, the universe, and God. It does not belong to this nation yet. Therefore, according to the writer, the struggle for that must always be done in order to the heart and the common sense. become the safer of this nation.